TPEN/TPGS (T2) combo dramatically reduces Philadelphia chromosome‐positive pro‐lymphoblastic B leukemia in BALB/c mice (2022)
ABSTRACT: Acute lymphoblastic leukemia (ALL) is hematological neoplasia that afects human beings from early life to adulthood. Although ALL treatment has been efective, an important percentage of ALL patients are resilient to treatment. Therefore, there is an urgent need for testing a new combination of compounds for the treatment of this disease. Recently, combined TPEN and TPGS (T2 combo) have shown selective cytotoxic efects in vitro leukemia cells such as Jurkat, K562, and Ba/F3 cells. In this study, we aimed to test the efect of combined TPEN and TPGS agents (T2 combo) at a fxed dose (TPEN 5 mg/ kg: TPGS 100 mg/kg) on leukemic Ba/F3-BCR-ABL P210 BALB-c mice model. We found that 4 successive 2-day apart intravenous injections of T2 combo showed a statistically signifcant reduction of Ba/F3 BCR-ABL leukemia cells (− 69%) in leukemia BALB/c mice (n=6) compared to untreated leukemia group (n=6). Moreover, the T2 combo was innocuous to non-leukemia BALB/c mice (n=3) compared to untreated non-leukemia mice (control, n=3). After treatments (day 42), all mice were left to rest until day 50. Outstandingly, the leukemia BALB/c mice treated with the T2 combo showed a lower percentage of Ba/F3-BCR-ABL P210 cells (− 84%) than untreated leukemia BALB/c mice. Furthermore, treatment of leukemia and non-leukemia mice with T2 combo showed no signifcant tissue alteration/damage according to the histo pathological analysis of brain, heart, liver, kidney, and spleen samples; however, T2 combo signifcantly reduced the number of leukocytes in the bone marrow of treated leukemia mice. We conclude that the T2 combo specifcally afects leukemia cells but no other tissue/organs. Therefore, we anticipate that the T2 combo might be a potential pro-oxidant combination for the treatment of leukemia patients.